Predictors of Post-operative Mycetoma Recurrence Using Machine-Learning Algorithms: The Mycetoma Research Center Experience. - Ali Wadal; Tusneem Ahmed Elhassan; Hajer Ahmed Zein; Manar Elsheikh Abdel-Rahman; Ahmed Hassan Fahal (Public Library of Science (PLoS), 2016)
Post-operative recurrence in mycetoma after adequate medical and surgical treatment is common and a serious problem. It has health, socio-economic and psychological detrimental effects on patients and families. It is with this in mind, we set out to determine the predictors of post-operative recurrence in mycetoma. The study included 1013 patients with Madurella mycetomatis causing eumycetoma who underwent surgical excision at the Mycetoma Research Centre, Khartoum, Sudan in the period 1991-2015. The clinical records of these patients were reviewed and relevant information was collected using a pre-designed data collection sheet. The study showed, 276 patients (27.2%) of the studied population developed post-operative recurrence, 217 were males (78.6%) and 59 were females (21.4%). Their age ranged between 5 to 70 years with a mean of 32 years. The disease duration at presentation ranged between 2 months and 17 years. The majority of the patients 118 (42.8%) had mycetoma of 1 year duration. In this study, students were the most affected; 105 (38%) followed by workers 70 (25.4%), then farmers 48(17.3%). The majority of the patients were from the Central Sudan 207 (75%), Western Sudan 53 (19.2%) while 11 patients (4%) were from the Northern part. Past history of surgical intervention performed elsewhere was reported in 196 patients (71.1%). Family history of mycetoma was reported in 50 patients (18.1%). The foot was the most affected site, 245 (88.7%), followed by the hand seen in 19 (6.8%) patients and 44 (4.5%) had different sites involvement. Most of the patients 258 (93.5%) had wide local surgical excisions while 18 had major amputation. The model predicted that the certain groups have a high risk of recurrence, and these include patients with disease duration greater than 10 years and extra-pedal mycetoma. Patients with disease duration between [5-10] years, with pedal mycetoma, who had previous surgery, with positive family history and underwent wide local surgical excision. Patients with disease duration [5-10] years, with pedal mycetoma, had previous surgery, with no family history but presented with a disease size (> 10 cm), were non- farmers and underwent wide local surgical excision. Other groups are patients with disease duration (≤5 years), with pedal mycetoma, age <59 years, living in the Western /Eastern / Southern regions of the Sudan and with positive family history and had wide local surgical excision. Also included patients with disease duration (≤5 years), with pedal mycetoma, aged <59 years, living in the northern or central region, with no family history but presented with a disease size >10 cm, working as farmers or students and underwent wide local surgical excision. In conclusion, these groups of patients need special care to reduce the incidence of post-operative recurrence with its morbidity and detrimental consequences. In depth studies for the other predisposing factors for post-operative recurrence such as genetic, immunological and environmental factors are needed.